Dinamika Peradaban, Pemikiran, dan Perkembangan Pendidikan Islam pada Masa Kejayaan Kerajaan Banten - Fikri Fathul Aziz; Irfan Maulana Adnan; Wahyu Sihab (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the dynamics of Islamic education during the Sultanate of Banten, an Islamic kingdom that developed since the 16th century and became one of the centers of Islamic civilization in the archipelago. Islamic education in Banten not only shapes the Islamic identity of the community, but also strengthens morality, social solidarity, and cultural resilience. Islamic boarding schools are the main pillars of education that integrate the teaching of religious science, character education, and socio-religious practices. The role of pesantren expands, not only as a learning center, but also as a da'wah institution that instills the values of independence, justice, and brotherhood in the midst of a multicultural society. Great scholars such as Sheikh Nawawi al-Bantani and Sheikh Yusuf al-Makassari have an important role in strengthening the scientific network between Banten, the Middle East, and the Islamic world. Their profound works in the fields of jurisprudence, Sufism, and morals had a great influence on the development of Islamic thought in Southeast Asia. The pesantren curriculum that focuses on the yellow book, with the teaching methods of sorogan, bandongan, and wetonan, produces students who are not only knowledgeable, but also disciplined, moral, and sensitive to social problems. The Dutch colonial period brought severe challenges with secular policies and restrictions on Islamic education. However, pesantren still exist as spiritual and intellectual fortresses. This success is supported by the ability of pesantren to develop economic independence and expand scientific networks through the overseas migration of students to various Islamic study centers abroad. Until now, Banten's Islamic education heritage has transformed into a modern Islamic boarding school that is able to combine classical traditions with technology and global insights. This study confirms that traditional Islamic education in Banten has a strategic role in shaping the social, spiritual, and identity structure of the Muslim community, which persists across generations.